Analisis Efektivitas Sistem Kontrol Aquascape Berbasis IoT dengan Pencahayaan Adaptif Dibandingkan Metode Konvensional - Farah Fairuz (Fakultas Ilmu Komputer, 2026)
Aquascapes placed in public service areas require lighting that preserves their visual function without unnecessarily extending light exposure. Conventional lighting operated continuously may increase the duration of light exposure and potentially support algal formation on the aquarium glass. This study aimed to design an adaptive Internet of Things (IoT)-based lighting system and to compare its performance with conventional lighting. A Research and Development method was applied through a limited seven-day trial using two aquascapes prepared under equivalent initial conditions. The first treatment used an ESP32 microcontroller, a Passive Infrared (PIR) sensor, a relay, an LED lamp, and temperature and pH sensors connected to the Blynk platform; the lamp turned on when user presence was detected and turned off after a specified period without movement. The second treatment used an LED lamp operated continuously for 24 hours per day. The primary data consisted of the total lamp operating duration and the algal coverage on the glass, measured once on day 7 using ImageJ; laminated white paper was used only as a background behind the glass during photography. Temperature, pH, and fish survival rate were recorded as supporting data. Results showed that the total lamp operating duration was 249 minutes under adaptive lighting and 10,080 minutes under conventional lighting, a reduction of 97.53%. Observation on day 7 indicated an algal coverage of 0.00% under adaptive lighting and 2.15% under conventional lighting. Temperature and pH remained relatively stable under the adaptive system, and the survival rate reached 100% in both treatments. The study concludes that the IoT-based adaptive lighting system operated as designed and effectively reduced lighting duration, with an initial indication of lower algal coverage during the limited trial.
:: Finalisasi file repositori 28 Juli 2026_Kurnadi
Keywords: Adaptive lighting; Algal coverage; Aquascape; Internet of Things; PIR sensor